Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose that $Y_1,Y_2,\ldots,Y_n$ are independent $\mathcal{N}(\alpha x_i,\sigma^2)$ variates where $x_1,x_2,\ldots,x_n$ are known constants. Show that the likelihood ratio statistics for testing a value of $\alpha$ is given by $D=n \log (1+\left(\frac{1}{n-1} T^2\right))$, where $T=(\hat{\alpha}{−\alpha})/\sqrt{s^2 \cdot c}$ where $c=\left(\sum_{i} x_i^2\right)^{-1}$.

Hint: you will need to show that $\sum_i (y_i{-\alpha} x_i)^2 = \sum (y_i - \hat{\alpha}{x_i})^2+(\hat{\alpha}{-\alpha})^2 \sum(x_i^2)$

share|cite|improve this question
If you don't get any satisfiable answers in a day, I suggest you post it on – Kirthi Raman Mar 14 '12 at 22:35

Suppose that $y_1,\ldots,y_n$ are observations from $Y_1,\ldots,Y_n$. Then the likelihood function is $$ L(\alpha,\sigma^2)=\prod_{i=1}^n \,(2\pi \sigma^2)^{-1/2}\exp\left(-\frac{1}{2\sigma^2}(y_i-\alpha x_i)^2\right). $$ When $(\alpha,\sigma^2)$ are allowed to vary in $\mathbb{R}\times (0,\infty)$ the likelihood function attains it maximum at $L(\hat{\alpha},\hat{\sigma}^2)$ where $\hat{\alpha}$ and $\hat{\sigma}^2$ are the maximum likelihood estimates, i.e. $$ \hat{\sigma}^2=\frac{1}{n}\sum_{i=1}^n(y_i-\hat{\alpha}x_i)^2. $$ Under the hypothesis that $\alpha$ is a fixed real number, the likelihood function attains its maximum in $L(\alpha,\tilde{\sigma}^2)$, where $$ \tilde{\sigma}^2=\frac{1}{n}\sum_{i=1}^n(y_i-\alpha x_i)^2. $$ The likelihood ratio is then (using the hint) $$ Q=\frac{L(\alpha,\tilde{\sigma}^2)}{L(\hat{\alpha},\hat{\sigma}^2)}=\frac{(2\pi\tilde{\sigma}^2)^{-n/2}\exp\left(-\frac{1}{2\tilde{\sigma}^2}\sum_{i=1}^n (y_i-\alpha x_i)^2\right)}{(2\pi\hat{\sigma}^2)^{-n/2}\exp\left(-\frac{1}{2\hat{\sigma}^2}\sum_{i=1}^n (y_i-\hat{\alpha} x_i)^2\right)}\\ =\left(\frac{\sum_{i=1}^n(y_i-\alpha x_i)^2}{\sum_{i=1}^n(y_i-\hat{\alpha}x_i)^2}\right)^{-n/2}\frac{e^{-n/2}}{e^{-n/2}}\\ =\left(1+\frac{(\hat{\alpha}-\alpha)^2\sum_{i=1}^n x_i^2}{\sum_{i=1}^n(y_i-\hat{\alpha}x_i)^2}\right)^{-n/2} $$ Thus $Q=(1+\frac{1}{n-1}T^2)^{-n/2}$ and $-2\log Q=n\log(1+\frac{1}{n-1}T^2)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.